PREVELENCE OF DEPRESSION AMONG TYPE II DIABETES PATINETS IN A MEDICAL COLLEGE HOSPITAL IN JHARKHAND. - Kumar, Anil; Anand, Chhitiz; Mahli, Rajiv Kumar (Student’s Journal of Health Research Africa, 2024)
Background Diabetes and depression are both very serious chronic conditions that decrease the quality of life, increase functional disability, and decrease life expectancy. Though this association is well established, results from developing country like India and especially eastern India, where poor socio-economic status, lower literacy and patient compliance is a major factor hindering treatment are limited. We aim to study the prevalence of depression among type 2 diabetes patients’ in our center Methods This prospective study was conducted in a SBMC Hazaribagh. Ninety-nine previously diagnosed Type II diabetes patients aged 30years and above and not meeting the exclusion criteria between1st July2021 and 30th September2021 were interviewed. Patients with known psychiatric disorders on treatment were excluded from the study. Patient Health Questionnaire (PHQ)-9 questionnaires was used to screen for depression. Results Our cohort comprised of 99 patients with median age of 55years (Range: 19-82years) with a Male: Female of 1.06:1. Our study found an incidence of 70% of varying grades of depression among type 2 diabetes patients, with 40% having mild and 54% moderate depression. None of our patients had severe depression. No statistically significant association between incidence of depression among various age and gender groups was found. A significant association was noted for the incidence with duration of illness. No significant association between incidence of depression and socio- economic status, regular follow-up, co-existing hypertension and co- existence of other diabetes related complications were noted. Conclusion Depression is a significant problem among diabetic patients. Early identification and referral for further evaluation and management can remarkably improve the quality of life of such patients’ and decrease the care given burden.